Empowering Rural Communities Through Digital Literacy Initiatives in India - Digvijay Pandey (International Assulta of Research and Engagement (IARE), 2023)
India, as one of the countries with the largest population in the world, faces major challenges in increasing digital literacy in rural areas. Inequality of access and understanding of information technology can hinder social and economic development in rural communities. Therefore, community service through digital literacy initiatives is important to overcome this problem. This article aims to document and analyze community service efforts in increasing digital literacy in rural Indian communities. The main goal is to empower rural communities with basic skills and knowledge of digital technologies so they can access educational opportunities, employment, and online services more effectively. The service method uses Asset Bassed Community Development (ABCD) involving collaboration between educational institutions, non-governmental organizations, and local communities. These programs include practical training, workshops, and access to digital resources. The results of this service showed a significant increase in understanding of digital technology among the participating rural Indian communities. Program participants actively use digital devices for educational purposes, job searches, and communicating with government and health services. Additionally, there is increasing awareness of the economic potential that can be gained through digital literacy skills. So, it is concluded that digital literacy initiatives that focus on community service have great potential to empower rural communities in India. Through collaboration between various parties, rural communities can be given the tools they need to participate in the digital era, reducing inequality of access and opening the door to new opportunities. This article underscores the continued importance of such community service efforts to support inclusive development in India.